2011
DOI: 10.1260/1747-9541.6.4.553
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Practice for Technique Adaptation in Expert Performers

Abstract: Coaches traditionally rely on explicit approaches (e.g., instruction, video feedback) to adapt technique in skilled athletes. While such methods can generate relatively rapid learning outcomes, the resultant technical execution is susceptible to breakdown under competition pressure. An alternative approach is to use ‘implicit motor learning’ in which adaptations occur without conscious knowledge of the underlying rules and the newly learned skill is less likely to breakdown under pressure. However, research ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…If control over the target variable remained largely subconscious, as is thought ideal for performance (Csikszentmihalyi, 1990;Swann, Crust, Keegan, Piggott, & Hemmings, 2015), it would be difficult to see how any long-term changes could be initiated. Indeed, Rendell, Farrow, Masters, and Plummer (2011) have demonstrated the limitations of implicit strategies in this particular context. More specifically, athletes counting the number of tones overlaid on music soundtracks (i.e., an effort not to think about the movement) during netball shooting practice to a higher than regulation ring led to an eventual lower ball flight trajectory instead of an intended higher trajectory, despite athletes not being aware of any change taking place.…”
Section: Aim: Deautomate the Erroneous (Well-established) Techniquementioning
confidence: 99%
“…If control over the target variable remained largely subconscious, as is thought ideal for performance (Csikszentmihalyi, 1990;Swann, Crust, Keegan, Piggott, & Hemmings, 2015), it would be difficult to see how any long-term changes could be initiated. Indeed, Rendell, Farrow, Masters, and Plummer (2011) have demonstrated the limitations of implicit strategies in this particular context. More specifically, athletes counting the number of tones overlaid on music soundtracks (i.e., an effort not to think about the movement) during netball shooting practice to a higher than regulation ring led to an eventual lower ball flight trajectory instead of an intended higher trajectory, despite athletes not being aware of any change taking place.…”
Section: Aim: Deautomate the Erroneous (Well-established) Techniquementioning
confidence: 99%
“…Importantly, a study by Rendell et al (2011) showed that implicit learning was effective in improving already learned sport-specific techniques also in expert performers (professional netball players). Gabbett and Masters (2011) described several possible effective strategies for improving implicit learning such as the use of errorless learning (learning without mistakes through step-by-step introducing of parts of a new skill), random practice (flexible working on skills, instead of a logical structure during training) or using dual-tasks to avoid step-by-step learning of a specific skill.…”
Section: Discussionmentioning
confidence: 99%
“…Explicit learning is the learning of new skills using explicit instructions and rules, resulting in declarative knowledge and the ability to articulate how to perform the skill (Liao & Masters, 2001). In contrast, implicit learning is learning unconsciously, without instruction and rules, leading to few declarative knowledge (Reber, 1989;Rendell, Farrow, Masters, & Plummer, 2011). A review of Reber (2013) summarised existing literature on neural substrates of implicit and explicit motor learning and reported that implicit motor learning reflects general plasticity of neuronal circuits.…”
Section: Introductionmentioning
confidence: 99%
“…As such, data are provided to inform applied coaching practice about what to avoid (see also Rendell, Farrow, Masters, & Plummer, 2011). Crucially from this case study, is the strong influence that Peter's mind-set had on the process.…”
Section: Brief Discussion Of Case Studymentioning
confidence: 99%